2007
DOI: 10.1210/jc.2007-0944
|View full text |Cite
|
Sign up to set email alerts
|

Increased Daytime Somnolence despite Normal Sleep Patterns in Patients Treated for Nonfunctioning Pituitary Macroadenoma

Abstract: Daytime sleepiness is increased despite normal sleep patterns in patients treated for NFMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…In addition, the daytime sleepiness scores in our patients were comparable to scores found in patients treated for other pituitary tumors or cerebral diseases such as nonfunctioning adenomas [16], craniopharyngeoma [23], hypothalamic tumors [23], subarachnoid haemorrhage [24], or traumatic brain injury [25], indicative for the relationship between cerebral disease in general and increased daytime sleepiness.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, the daytime sleepiness scores in our patients were comparable to scores found in patients treated for other pituitary tumors or cerebral diseases such as nonfunctioning adenomas [16], craniopharyngeoma [23], hypothalamic tumors [23], subarachnoid haemorrhage [24], or traumatic brain injury [25], indicative for the relationship between cerebral disease in general and increased daytime sleepiness.…”
Section: Discussionsupporting
confidence: 78%
“…Each patient was also asked to provide a healthy control person of comparable age and sex, who did not use any medication, to serve as a control group with a comparable socio-economic status. The control group was extended with controls derived from other studies in our center who were approached similarly [16].…”
Section: Protocolmentioning
confidence: 99%
“…[1] As more survivors live to adulthood, late effects of disease and treatment negatively impact quality of life. [2-5] Poor sleep quality, and its effects, such as daytime sleepiness, are often reported late effect of brain tumor survivors, [6-9] and may affect quality of life by decreasing participation in life events such as school, athletics, and/or social activities. A recent study by van der Klaauw et al reported that increased sleepiness (as measured by the Epworth Sleepiness Scale) in survivors of nonfunctioning pituitary adenomas was associated with 15 of 21 quality of life (QoL) subscores from four validated QoL questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by van der Klaauw et al reported that increased sleepiness (as measured by the Epworth Sleepiness Scale) in survivors of nonfunctioning pituitary adenomas was associated with 15 of 21 quality of life (QoL) subscores from four validated QoL questionnaires. [9] Poor sleep quality and daytime sleepiness in childhood cancer survivors is also associated with neurocognitive deficits such as impaired task efficiency, diminished organization and impaired memory. [6] Clanton et al reported that the effect of sleepiness and poor sleep quality on neurocognitive outcomes is evident even after adjusting for cranial radiation therapy, steroids and antimetabolite chemotherapy, sex, and current age.…”
Section: Introductionmentioning
confidence: 99%
“…Each patient was asked to provide a control person of comparable sex and age. In addition, for every patient, one age- and sex-matched control subject was derived from a database containing results of similar questionnaires in healthy controls in our center [19]. The medical ethics committee of the Leiden University Medical Center approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%